Silicon Asymmetric Membranes for Efficient Lithium Storage: A Scalable Method. Issue 4 (12th November 2015) - Wu, Ji; Chen, Hao; Padgett, Clifford
Abstract: In this study, scalable membrane technologies are adapted to obtain silicon asymmetric membranes for lithium‐ion battery anodes. The unique asymmetric porous structure can provide both mechanical support and free volume to accommodate the large volume expansion during silicon lithiation, thus leading to excellent rate and cycling performance. An overall specific capacity as high as 1500 mAh g −1 was achieved at 100 mA g −1 . Even at 1000 mA g −1, the capacity was still above 800 mAh g −1 . More than 90 % of the initial capacity was retained after 200 cycles. It was also observed that a lower Si content and higher carbonization temperature can help achieve stable cycling performance in general. This report is significant in terms of demonstrating a simplistic, generic, and scalable method to create a robust, porous asymmetric membrane structure for efficient lithium‐ion storage. Abstract : Silicon asymmetric membranes : In this study, highly scalable membrane technology is adapted to obtain asymmetric membranes made of inorganic silicon for high performance lithium‐ion battery anodes. A high overall specific capacity is obtained at 100 mA g −1, and more than 90 % of the initial capacity is retained after 200 cycles. Such a simple, efficient, and scalable method brings unlimited potential towards commercializing Si‐based anode materials for next‐generation lithium‐ion batteries.